CXCL12/CXCR4 facilitates perineural invasion via induction of the Twist/S100A4 axis in salivary adenoid cystic carcinoma. Issue 16 (25th June 2021) - Zhang, Mei; Zheng, Min; Dai, Li; Zhang, Wei‐long; Fan, Hua‐yang; Yu, Xiang‐hua; Pang, Xin; Liao, Peng; Chen, Bing‐jun; Wang, Sha‐sha; Cao, Ming‐xin; Ma, Xiang‐rui; et al.
Abstract: The activation of CXCL12/CXCR4 axis participated in the progression of multiple cancers, but potential effect in terms of perineural invasion (PNI) in SACC remained ambiguous. In this study, we identified that CXCL12 substantially expressed in nerve cells. CXCR4 strikingly expressed in tumour cells, and CXCR4 expression was closely associated with the level of EMT‐associated proteins and Schwann cell hallmarks at nerve invasion frontier in SACC. Activation of CXCL12/CXCR4 axis could promote PNI and up‐regulate relative genes of EMT and Schwann cell hallmarks both in vitro and in vivo, which could be inhibited by Twist silence. After overexpressing S100A4, the impaired PNI ability of SACC cells induced by Twist knockdown was significantly reversed, and pseudo foot was visualized frequently. Collectively, the results indicated that CXCL12/CXCR4 might promote PNI by provoking the tumour cell to differentiate towards Schwann‐like cell through Twist/S100A4 axis in SACC.